2003
DOI: 10.21273/jashs.128.2.0213
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Race Specific Resistance to Phytophthora Root Rot and Foliar Blight in Capsicum annuum

Abstract: Despite extensive breeding efforts, no pepper (Capsicum annuum L. var. annuum) cultivars with universal resistance to phytophthora root rot and foliar blight (Phytophthora capsici Leon) have been commercially released. A reason for this limitation may be that physiological races exist within P. capsici, the causal agent of phytophthora root rot and phytophthora foliar blight. Physiological races … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 14 publications
2
106
0
2
Order By: Relevance
“…The existence of diverse pathogen populations and physiological races within P. capsici has limited development of resistant cultivars of economically important hosts (Walker and Bosland 1999;Oelke and Bosland 2003). Since resistant host varieties may perform well in the presence of isolates from a certain region, but not with isolates from another region, breeders need to use a wide variety of P. capsici isolates to develop resistant varieties (Foster and Hausbeck 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of diverse pathogen populations and physiological races within P. capsici has limited development of resistant cultivars of economically important hosts (Walker and Bosland 1999;Oelke and Bosland 2003). Since resistant host varieties may perform well in the presence of isolates from a certain region, but not with isolates from another region, breeders need to use a wide variety of P. capsici isolates to develop resistant varieties (Foster and Hausbeck 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The spatial distribution of P. capsici isolates differing in virulence will also dictate how resistant varieties should be deployed (Foster and Hausbeck 2010). Previous studies have reported differences in virulence and pathogenicity among P. capsici isolates on vegetable hosts (Kim and Hwang 1992;Oelke and Bosland 2003;Palloix et al 1988;Reifschneider et al 1986;Ristaino 1990). Isolate virulence responses vary by host.…”
Section: Introductionmentioning
confidence: 99%
“…(Leonian 1922;Erwin and Ribeiro 1996). Economically, it is one of the most destructive pepper pathogens worldwide, attacks tomatoes and cucurbits as well, and has caused billions of dollars in damage to crops in the United States (Tyler 2002;Oelke et al 2003). Control is based primarily on the use of mefanoxam, cultural practices such as drip irrigation and black plastic mulch, and the use of genetically resistant varieties.…”
Section: Introductionmentioning
confidence: 99%
“…Since most species in the genus Capsicum are susceptible to different races of P. capsici (Oelke et al 2003) their relationship could be defined as a compatible interaction. Most common plant defence responses include alkalinisation of the extracellular medium (Felix et al 1993), explosive production of reactive oxygen species (Davies et al 2006), activation of signal transduction pathways such as the MAPK pathway (Eckardt 2002), and induction of defence-related genes (Eckardt 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the genus Capsicum, where there are almost no true resistant species, the disease has been managed by cultural practices or the use of fungicides (Hausbeck and Lamour 2004); however, none of these strategies has been effective as they have only reduced the incidence (Hausbeck and Lamour 2004), and fungicide-resistant isolates have appeared (Parra and Ristaino 2001). Thus, significant attention has been focused on the development of stable Phytophthora-resistant pepper cultivars (Oelke et al 2003). In this respect, numerous breeding programmes have attempted to find sources of resistance; nevertheless, none of the pepper 'resistant' cultivars currently available shows consistent high levels of resistance (Thabuis et al 2004).…”
Section: Introductionmentioning
confidence: 99%